2014
DOI: 10.4103/0973-1296.133275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cholinesterase activity of the standardized extract of Syzygium aromaticum L.

Abstract: Background:Clove (Syzygium aromaticum) is a well-known culinary spice with strong aroma; contains a high amount of oil known as clove oil. The major phyto-constituent of the clove oil is eugenol. Clove and its oil possess various medicinal uses in indigenous medicine as an antiseptic, anti-oxidant, analgesic and neuroprotective properties. Thus, it draws much attention among researchers from pharmaceutical, food and cosmetic industries.Objective:The aim of the present study was to determine the anti-cholineste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The increase in the brain AChE activity following aluminium exposure of rats was attributed to an allosteric interaction between Al with the peripheral anionic site of the enzyme molecule (50). The ability of eugenol to directly suppress the enhanced AChE activity following Al intoxication in the current study could be explained with the finding of an in vitro study that demonstrated a potential anti-cholinesterase property of eugenol (51). Similarly, eugenol was found to normalise the cortical AChE level in acrylamide-induced brain neuropathy in rats (21).…”
Section: Figure 3 Effect Of Eugenol And/or Aluminium On Brain Acetylcsupporting
confidence: 58%
“…The increase in the brain AChE activity following aluminium exposure of rats was attributed to an allosteric interaction between Al with the peripheral anionic site of the enzyme molecule (50). The ability of eugenol to directly suppress the enhanced AChE activity following Al intoxication in the current study could be explained with the finding of an in vitro study that demonstrated a potential anti-cholinesterase property of eugenol (51). Similarly, eugenol was found to normalise the cortical AChE level in acrylamide-induced brain neuropathy in rats (21).…”
Section: Figure 3 Effect Of Eugenol And/or Aluminium On Brain Acetylcsupporting
confidence: 58%
“…Analgesia produced by EOEC in the acute corneal pain appears to depend on its cholinergic activity, since EOEC effect was completely antagonized by the muscarinic cholinergic receptor antagonist atropine. In vitro studies of clove oil and eugenol have shown potent anti-acetylcholinesterase property ( 29 30 ). Since cholinergic system activation by muscarinic agonist or cholinesterase inhibitors have shown to produce analgesic effects, anti-acetylcholinesterase activity of EOEC and eugenol might also be in agreement with its mechanisms of their antinociception ( 31 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…While in MFA eugenol, methyl eugenol, myristic acid, galbacin and β-sitosterol were identified as an AChE inhibiting compounds. These identified compounds showed potent AChE inhibitory activity (Cuong et al, 2014;Mukherjee et al, 2014;Ayaz et al, 2017;Vargas-Méndez et al, 2019). TLC-MS-bioautography is a simple and fast method to identify bioactive compounds showing AChE activity.…”
Section: Discussionmentioning
confidence: 99%